96.3k views
5 votes
Let f(x)= x - 4 and g(x) = 6 - X
Evaluate the following.
f(g(-3))

User Jeantimex
by
5.3k points

2 Answers

4 votes

Answer: 5

Explanation:

g(x) = 6 - x

g(-3) = 6 - (-3)

= 6 + 3

= 9

f(x) = x - 4 f(g(-3)) = f(9)

f(9) = 9 - 4

= 5

User Tarquinius
by
5.2k points
3 votes

Answer:

f(g(-3)) = 5

Explanation:

To find f(g(x)) just plug in g(x) for x in f(x)

f(x)= x - 4

f(g(x)) = (6 - x) - 4

f(g(x)) = 6 - x - 4

f(g(x)) = 2 - x

Now to find f(g(-3)) we plug in -3 for x.

f(g(-3)) = 2 - (-3)

f(g(-3)) = 2 + 3

f(g(-3)) = 5

User SofaKng
by
5.5k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.